2022
DOI: 10.3390/molecules27030740
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hop Phenolic Compounds on Dry Hopping Beer Quality

Abstract: Background: The article considers the phenolic hop compounds’ effect on the quality indicators of finished beer. The topic under consideration is relevant since it touches on the beer matrix colloidal stability when compounds with potential destabilizing activity are introduced into it from the outside. Methods: The industrial beer samples’ quality was assessed by industry-accepted methods and using instrumental analysis methods (high-performance liquid chromatography methods—HPLC). The obtained statistical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Li et al [ 20 ] investigated the sensory quality of red wine with tannin and concluded that the wine with hydrolyzed tannin received high ratings for aroma and bouquet, and that it would enhance the taste balance and have a pleasant aftertaste. Previous research suggests that excessive amounts of glycosides, catechins, and other compounds can contribute to the bitterness of wine [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [ 20 ] investigated the sensory quality of red wine with tannin and concluded that the wine with hydrolyzed tannin received high ratings for aroma and bouquet, and that it would enhance the taste balance and have a pleasant aftertaste. Previous research suggests that excessive amounts of glycosides, catechins, and other compounds can contribute to the bitterness of wine [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The LC-MS analysis performed allowed us to putatively identify beer compounds ( Table S1 ). Among the sixty-two compounds identified, twenty-seven were classified as PC and fifteen as nonphenolic compounds ( Table 3 and Table 4 ), and some of these compounds are already established as astringent and/or bitter compounds [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Nineteen compounds were shown to be shared by all of the studied beers, but only thirteen PCs and ten non-PCs have already been described as astringent and/or bitter ( Table 3 and Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding beer, while there are data linking PC content to astringency and bitterness properties in humans [ 32 , 33 , 34 ], there is a lack of understanding about the molecular events involving the SPs inside the oral cavity that underpin these perceptions. So, this work is focused on deepening the knowledge on astringency and bitterness perception toward PCs’ interaction with SPs.…”
Section: Introductionmentioning
confidence: 99%
“…According to Goiris et al [ 75 ], various fractions of polyphenols are characterized by different effects on taste, ranging from imparting fullness of flavor to astringency. This issue was further explored by Gribkova et al [ 76 ]. The authors suggested that a combination of bitter resins, prenylflavonoids, and catechins is probably responsible for sharp astringency.…”
Section: Chemical Composition Of Hopsmentioning
confidence: 99%
“…The authors suggested that a combination of bitter resins, prenylflavonoids, and catechins is probably responsible for sharp astringency. Catechin, quercetin, and rutin, associated with soluble nitrogen and β-glucan dextrins, are at least partially responsible for residual bitterness [ 73 , 74 , 76 , 77 ].…”
Section: Chemical Composition Of Hopsmentioning
confidence: 99%